Bioactivites of two common polyphenolic compounds: Verbascoside and catechin. (2nd April 2016) - Sipahi, Hande; Gostner, Johanna M.; Becker, Kathrin; Charehsaz, Mohammad; Kirmizibekmez, Hasan; Schennach, Harald; Aydin, Ahmet; Fuchs, Dietmar
Abstract: Context : Natural products can present remarkable biological and pharmacological activities. In traditional medicine, plants have been used historically in treating cancer, infections, and other inflammatory conditions. Objective : Verbascoside and catechin are widespread polyphenolic plant compounds that could play a role in the anti-inflammatory and health-promoting effects of plants and plant extracts. Materials and methods : This study compares the potential cytotoxic effects of polyphenols verbascoside and catechin (6.25–200 µM) on human peripheral blood mononuclear cells (PBMC) for 48 h and myelomonocytic THP-1 and THP-1 Blue cells for 24 h. The effects of the compounds on immune activation markers such as indoleamine 2, 3-dioxygenase (IDO) activity as well as on neopterin formation and nuclear factor-κB (NF-κB) activation were investigated. Cytotoxicity of the compounds was tested using Cell-Titer Blue assay. Results : Verbascoside exhibited significant suppressive effects in mitogen-stimulated PBMC on tryptophan breakdown (>50 µM; IC50 value: 58.6 µM) and the production of neopterin (>6.25 µM; IC50 value: 217 µM). These effects correlated with a decline in cell viability, while THP-1 Blue cells were less sensitive. NF-κB activity was slightly enhanced at lower concentrations (<50 µM verbascoside) in stimulated cells and at the highest concentration used in unstimulated cells. Catechin had no relevant effects on cell viability and on the tested inflammation markers, except NF-κB activation in THP-1 Blue cells. Discussion and conclusion : The results obtained show that verbascoside and catechin represent effective compounds which interfere with immunobiochemical pathways that are highly relevant for immunosurveillance and competing virus infections.